Determinasi Promosi, Persepsi Harga, dan Kualitas Layanan Terhadap Kepuasan Pelanggan dengan Mediasi Keputusan Pembelian - Ramadhan, Habib Fitra; Murtiasih, Sri (ARBITRASE: Journal of Economics and Accounting, 2025)
The development of digital technology, particularly application-based services, has transformed the way people meet their daily needs, including food ordering. ShopeeFood, as a food delivery service in Indonesia, competes fiercely with GoFood and GrabFood, which have previously dominated the market. To attract customers, ShopeeFood implements strategies such as promotions, competitive pricing, and improved service quality. These three factors promotion, price perception, and service quality play a role in influencing purchasing decisions and customer satisfaction. This study aims to analyze the influence of promotion, price perception, and service quality on customer satisfaction through purchasing decisions in ShopeeFood services in Depok City. The analytical method in this study uses quantitative primary data obtained from questionnaires distributed to 150 respondents. The analytical tools used include instrument testing, outer model testing, and inner model testing. The data analysis was carried out using SmartPls version 3 software. The results show that promotion and price perception have an influence on purchasing decisions, while service quality does not. All three variables (promotion, price perception, and service quality) significantly influence customer satisfaction. Purchasing decisions also affect customer satisfaction. Promotion and price perception influence customer satisfaction indirectly through purchasing decisions, while service quality has a direct effect on customer satisfaction without going through purchasing decisions.